In vitro synergy of isavuconazole in combination with colistin against Candida auris - Patrick Schwarz (Nature Portfolio, 2020)
Abstract The in vitro interactions of isavuconazole with colistin were evaluated against 15 clinical Candida auris isolates by a microdilution checkerboard technique based on the EUCAST reference method for antifungal susceptibility testing and by agar diffusion using isavuconazole gradient concentration strips with or without colistin incorporated RPMI agar. Interpretation of the checkerboard results was done by the fractional inhibitory concentration index and by response surface analysis based on the Bliss model. By checkerboard, combination was synergistic for 93% of the isolates when interpretation of the data was done by fractional inhibitory concentration index, and for 80% of the isolates by response surface analysis interpretation. By agar diffusion test, although all MICs in combination decreased compared to isavuconazole alone, only 13% of the isolates met the definition of synergy. Essential agreement of EUCAST and gradient concentration strip MICs at +/− 2 log2 dilutions was 93.3%. Antagonistic interactions were never observed for any technique or interpretation model used.